Cost management of service composition - MEDEIROS, Robson Wagner Albuquerque de (2017)
Service-Oriented Architecture (SOA) is a software design style based on the notion of Service-Oriented Computing (SOC) that facilitates the interoperability among computer systems of possibly different businesses. Cost is one of the most challenging factors inﬂuencing SOA adoption in organisations and a signiﬁcant factor in SOA project success. Nevertheless, many institutions across the world have adopted SOA to interconnect their computing infrastructures (Business-to-Business) and offer interfaces to their customers (Business-to-Customer). For these companies, SOA can address their needs to access the market more quickly, respond to changes in a business environment, improve business processes, improve customers’ services and even reduce costs. In SOA, service composition has emerged as an important strategy to enable collaboration of applications provided by different companies (Business-to-Business). With the increasing number of Web services having similar functionality but different pricing schemes, choosing the most appropriate set of services with the lowest cost has been a challenge in service compositions. Several techniques to compute and analyse the cost of service compositions already exist. However, there is still no approach to developing cost management systems able to assist in the planning, deﬁnition, scheduling, execution, monitoring and adaptation of compositions taking into account all classes of cost behaviour and all type of cost drivers. Thus, the principal objective of this thesis is to present a framework to manage cost throughout the service composition life-cycle in an integrated way taking into account cost properties of services and service compositions. Therefore, we provide a metamodel to specify complex cost behaviours. Also, we propose algorithms to compute service costs and select the best services that meet the cost requirements of the service composition according to the cost behaviour of each service. Moreover, we propose an architecture for developing engines able to manage the cost throughout the service composition life-cycle. Finally, we implemented a prototype based on the proposed architecture and executed experiments that show the effectiveness and efﬁciency of our approach to managing the cost of service composition.